2019
DOI: 10.1002/admi.201900378
|View full text |Cite
|
Sign up to set email alerts
|

Independent Two Way Switching of the Wetting Behavior of Cellulose‐Derived Nanoparticle Surface Coatings by Light and by Temperature

Abstract: light-triggered changes in the polarity of a material are of interest, as the switching mechanism does not rely on diffusion, as is the case with the pH-or electrolyteinduced switching of polyelectrolytes. [18] However, one of the major challenges of light-responsive spiropyran that has yet to be solved is the rather slow dynamics of the molecular rearrangements (i.e., slow switching behavior) and the oxidative degradation that can occur during the process. Another group of photoresponsive polarity-switching m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 36 publications
(41 reference statements)
1
26
0
1
Order By: Relevance
“…Further, by introducing micro and nanoscale hierarchical surface structures, Feng et al showed the reversible wetting switching between superhydrophilic and superhydrophobic states on TiO 2 nanorod films by cooperating micro and nano hierarchical surface structures together with a photosensitive material coating and the wettability change was quite similar to as reported in their previous work [49]. Morphology of hierarchical surface structures with micro and nano features can be clearly visualized from the SEM images shown in Figure 7e, f. Due to intrinsic photocatalytic property and reversible wettability switch, TiO 2 has also attracted much attention for its various applications, such as antifogging and self-cleaning [51][52][53][54][55]. Another simple approach to produce rough TiO 2 films was based on CF 4 plasma etching technique, which was adopted by Zhang et al to produce superhydrophilic and superhydrophobic patterns by UV irradiation using a photomask [56].…”
Section: (A B) Fe-sem Top-images Of the As-prepared Zno Nanorod Filmsupporting
confidence: 80%
“…Further, by introducing micro and nanoscale hierarchical surface structures, Feng et al showed the reversible wetting switching between superhydrophilic and superhydrophobic states on TiO 2 nanorod films by cooperating micro and nano hierarchical surface structures together with a photosensitive material coating and the wettability change was quite similar to as reported in their previous work [49]. Morphology of hierarchical surface structures with micro and nano features can be clearly visualized from the SEM images shown in Figure 7e, f. Due to intrinsic photocatalytic property and reversible wettability switch, TiO 2 has also attracted much attention for its various applications, such as antifogging and self-cleaning [51][52][53][54][55]. Another simple approach to produce rough TiO 2 films was based on CF 4 plasma etching technique, which was adopted by Zhang et al to produce superhydrophilic and superhydrophobic patterns by UV irradiation using a photomask [56].…”
Section: (A B) Fe-sem Top-images Of the As-prepared Zno Nanorod Filmsupporting
confidence: 80%
“…The photoisomerization of DASAs results in changes in solubility, polarity, and structure which are attractive for applications in many fields of chemistry. To date, these applications have included drug delivery, [ 19–21 ] surface modifications, [ 22,23 ] photo‐patterning, [ 24–26 ] catalyst recycling, [ 27 ] gate and molecular logic, [ 28–30 ] sensors, [ 31–35 ] nanoreactors, [ 36 ] and aggregation induced emission (AIE) materials. [ 37 ]…”
Section: Methodsmentioning
confidence: 99%
“…The developed composite could be switched reversibly between hydrophobic and hydrophilic properties through exposure to visible light. The coating can be applied onto papers and allow the production of paper-based fluid timers [ 162 ]. The incorporation of CNC and 2-bromoisobuuturyl bromide into 6-[4-(4-methoxyphenyl-azo) phenoxy] hexyl methacrylate produced a photo-responsive composite that changes in color through the irradiation to light with the wavelength of 350 nm [ 163 ].…”
Section: Cellulose-based Polymers In 4d Printing Technologymentioning
confidence: 99%